2012
DOI: 10.2478/s11536-011-0154-6
|View full text |Cite
|
Sign up to set email alerts
|

Coffee consumption and risk of stroke: a meta-analysis of cohort studies

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 25 publications
(30 reference statements)
0
7
1
6
Order By: Relevance
“…Habitual coffee consumption may raise the blood pressure [30]. Our results deviate from study conducted by Larsson et al [31] and Zhang et al [32] The Circadian pattern in onset of ischemic and hemorrhagic stroke showed a significant peak in morning (6 am-12 pm) and afternoon (12 pm-6 pm), respectively. The could be correlated to biological factors such as blood pressure (with physiological nocturnal decrease and morning increase), hemostatic balance (with increased platelet aggregability, increased level of hematocrit with hyperviscosity of blood in morning hypercoagulability, hypofibrinolysis) autonomic systemic activity (with activation of sympathetic nervous system after wake up movement with consequence on vascular tone, blood pressure, heart rate).…”
Section: Discussioncontrasting
confidence: 88%
“…Habitual coffee consumption may raise the blood pressure [30]. Our results deviate from study conducted by Larsson et al [31] and Zhang et al [32] The Circadian pattern in onset of ischemic and hemorrhagic stroke showed a significant peak in morning (6 am-12 pm) and afternoon (12 pm-6 pm), respectively. The could be correlated to biological factors such as blood pressure (with physiological nocturnal decrease and morning increase), hemostatic balance (with increased platelet aggregability, increased level of hematocrit with hyperviscosity of blood in morning hypercoagulability, hypofibrinolysis) autonomic systemic activity (with activation of sympathetic nervous system after wake up movement with consequence on vascular tone, blood pressure, heart rate).…”
Section: Discussioncontrasting
confidence: 88%
“…Focused on one specific food, and except for the reviews retained for main analysis, the others were excluded (n 3) There was no significant association between SSB consumption and total stroke Wu et al (2015) (15) Refined grains Risk of stroke 8 8284 410 821 A diet containing greater amounts of refined grains was not associated with risk of stroke and its subtypes Qin et al (2015) (17) Dairy products Risk of stroke 12 21 801 504 803 An inverse association was found between dairy consumption and stroke. Low-fat dairy products and cheese may protect against stroke Shi et al (2014) (12) Legumes (20) Red and processed meat Risk of stroke 5 9593 239 251 Consumption of red and/or processed meat increased risk of stroke, particularly ischaemic stroke Zhang et al (2012) (7) Coffee Risk of stroke 13 12 414 492 760 Coffee consumption at different levels reduces the risk of stroke Xun et al (2012) (5) Fish Risk of stroke 16 10 568 407 127 Fish intake may have a protective effect against the risk of stroke, particularly ischaemic stroke Shen et al (2012) (24) Tea (4) Red meat consumption Risk of stroke 6 10 630 329 495 Consumption of fresh red meat and processed red meat as well as total red meat is associated with increased risk of total stroke and ischaemic stroke, but not haemorrhagic stroke Larsson and Orsini (2011) (27) Coffee Risk of stroke 11 10 003 479 689 Moderate coffee consumption may be weakly inversely associated with risk of stroke Mellen et al (2008) (16) Whole…”
Section: Fruits and Vegetablesmentioning
confidence: 99%
“…Three reviews reported on the relationship between coffee and stroke (7,26,27) . Ding et al (26) performed a metaanalysis to assess the dose-response relationship between long-term coffee consumption and risk of CVD.…”
Section: Coffeementioning
confidence: 99%
See 1 more Smart Citation
“…Consumption has also recently been associated with increased all-cause mortality [7]. In contrast, recent epidemiological studies have suggested that regular coffee consumption could decrease the risk of type II diabetes, Parkinsonism, Alzheimer's disease, liver cancer, and even the risk of stroke [2], [8][10].…”
Section: Introductionmentioning
confidence: 99%